Sites of prehistoric life in Northern Ireland - Welsh, Henry (Archaeopress Publishing Ltd, 2018)
This monograph brings together information on all the currently known sites in Northern Ireland that are in some way associated with prehistoric life. Compiled from a number of sources, it includes many that have only recently been discovered. A total of 1580 monuments are recorded in the inventory, ranging from burnt mounds to hillforts.